3D Printing of A Thermally Programmable Conformal Metasurface (Adv. Mater. Technol. 7/2022). Issue 7 (12th July 2022) - Yin, Haoyu; Liang, Qingxuan; Duan, Yubing; Fan, Jun; Li, Zhaohui
Abstract : Curved Metasurfaces In article number 2101479, Qingxuan Liang and co‐workers demonstrate a thermally programmable conformal metasurface carpet cloak printed by the composite fused deposition molding. The thermal programming method effectively reduces the complexity of conformal manufacturing and ensures the electromagnetic performances of the metasurface. This work provides a viable implementation strategy for complex curved metasurface and will substantially promote the applications of the conformal invisibility cloaks.